Morphosyntactic Analysis of Political News on Political Misogyny in Indonesia in South China Morning Post - Wahyuni, Novi Sri; Mawarni, Heni (Universitas Muhammadiyah Mataram, 2024)
This study analyzes political news from the South China Morning Post using morphosyntactic analysis to examine political misogyny in Indonesia. The research objectives are to identify derivational and inflectional morphemes that appear in political news articles on the South China Morning Post online in November 2023. The study employed a qualitative design and content analysis methodology, with data sourced from online political news articles published by the South China Morning Post in November 2023. The researchers are the primary instrument of this study because they actively acquired and clustered the data, while the secondary data was an article data sheet. The researchers discovered 7 patterns of inflectional morphemes with 26 words in the data. Class-changing derivational words that are found in articles of political In Indonesia, claims against Joko Widodo’s wife highlight the nation’s history of ‘political misogyny’ on 30 November 2023 and are mostly suffixes rather than prefixes. In the article, there were 10 derivational words with 4 patterns, such as verb to adjective, adjective to noun, noun to verb, and adverb to adjective class-changing.